High expression of CXCR4, CXCR7 and SDF-1 predicts poor survival in renal cell carcinoma - Wang Linhui; Chen Wei; Gao Li; Yang Qing; Liu Bing; Wu Zhenjie; Wang Yang; Sun Yinghao (World Journal of Surgical Oncology, 2012)
Abstract Background Chemokines and their receptors are known to play important roles in the tumorigenesis of many malignancies. The aim of this study was to evaluate the prognostic impact of the expression of the chemokine SDF-1 and its receptors CXCR4 and CXCR7 in patients with renal cell carcinoma. Methods The expression of CXCR4, CXCR7 and SDF-1 in specimens from 97 renal cell carcinoma patients was evaluated by immunohistochemistry on a tissue microarray. These results were correlated with the clinicopathological parameters and survival of the patients. Results CXCR4 and CXCR7 were expressed in all patients, whereas SDF-1 was expressed in 61 patients (62.9%). No association was observed between the expression of CXCR4, CXCR7 or SDF-1 and the clinical or pathological data except between SDF-1 expression and Fuhrman’s grade (P = 0.015). Patients with high expression of CXCR4, CXCR7 and SDF-1 had shorter overall survival and recurrence-free survival than those with low expression. In a multivariate analysis, the high expression of CXCR4, CXCR7 and SDF-1 correlated with poor overall survival and recurrence-free survival independent of gender, age, AJCC stage, lymph node status, metastasis, histologic variant and Fuhrman’s grade. Conclusions High levels of CXCR4, CXCR7 and SDF-1 were associated with poor overall survival and recurrence-free survival in renal cell carcinoma patients. CXCR4, CXCR7 and SDF-1 may serve as useful prognostic markers and therapeutic targets for renal cell carcinoma.